Pengaruh Motivasi Non Material Terhadap Prestasi Kerja Pegawai Badan Pemberdayaan Masyarakat Desa di Kabupaten Gianyar - Suryawan, I Wayan Agus; Erviantono, Tedi; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2017)
ABSTRACT Motivations have an important role in improving employees work performance, one of them is by giving non-material motivation. The aim of this study was to determine the effect of non-material motivation to work performance. The method applied in this study was the associative method of quantitative approach with the intention in determining the influence of non-material motivation (X variable) on work performance (Y variable). The primary data in this study were obtained through a sample deployment with total samples of 54 employees at the Community Empowerment Agency in Gianyar regency. The analysis results of research findings showed that non-material motivation variable has positive and significant impacts on the employees’ work performances at the Community Empowerment Agency in Gianyar regency with the result of R2 was 71.0%, and the remaining 29.0% was influenced by other factors. The results of simple linear regression arithmetic showed that if the non-material motivation is constant, then the work performance will be 4,740. Meanwhile, if the non-material motivation is increased by 1%, automatically, the work performance will increase by 0.524. From the results of significant test was obtained that t count (11.285) is greater than t table (1.673) indicates that the non-material motivation has positive and significant impacts on the employees work performance at the Community Empowerment Agency in Gianyar regency. Keyword: Non-Material Motivation, Work Performance, Community Empowerment Agency in Gianyar regency